[OP.1B.10] INTRACRANIAL STENOSIS IN FIRST-GENERATION CHINESE MIGRANTS WITH NEWLY DIAGNOSED DIABETES. (September 2017) - Castellani, S.; Calabrese, M.; Boddi, M.; Marzotti, I.; Zhao, D.; Modesti, P.
Abstract : Objective: Ethnic differences might influence the value of current approach to cardiovascular risk stratification. Intracranial atherosclerotic disease was indeed reported as a common cause of ischemic stroke among patients of Asian ancestry and stroke incidence in China is high. However, no study investigated the prevalence of intracranial stenosis (ICS) in Chinese migrants with newly diagnosed DM and the screening of vascular lesions is still mainly focused on the more accessible extracranial carotid artery. Present survey was thus performed to determine the prevalence of intracranial stenosis in Chinese migrants with newly diagnosed diabetes. Design and method: A cross-sectional community-based survey enrolled Chinese first generation migrants (n = 1200) and native Italians (n = 291) aged 35–59 years. Hypertension was diagnosed according to ESH guidelines. Diagnosis of DM was based on fasting plasma glucose criteria (more than 125 mg/dl confirmed by repeat testing), and/or current treatment with glucose-lowering drugs. Chinese patients with newly diagnosed diabetes were screened for intracranial stenosis using Doppler ultrasound. ICS (any degree of stenosis) was diagnosed when the peak flow velocity at Transcranial Doppler (TCD) was higher than: 120 cm/s for anterior cerebral arteries (ACA); 155 cm/s for middle cerebral arteries (MCA); 100 cm/s for posterior cerebral arteries (PCA); 100 cm/s for basilar artery (BA); 90 cm/s for intracranial vertebral arteries (VA). Results: DM was diagnosed in 168 (14.0%) and 21 (7.3%) participants in the Chinese and Italian cohorts respectively (age- and gender adjusted OR 2.29; 95% C.L. 1.41 to 3.72). Difference was not reduced when obesity and socioeconomic indexes were included in the model. Ninety-six Chinese patients with newly diagnosed DM accepted to undergo the screening of cerebral vascular lesions. No patient had carotid stenosis of any degree wheres per-person prevalence of intracranial stenosis was 18.2%. Nine out of the 17 patients with any intracranial stenosis (52%) had more than 1 intracranial lesions. Conclusions: The high prevalence of asymptomatic intracranial stenosis in Chinese patients with newly diagnosed diabetes emphasizes the importance of paying attention to intracranial vessels in this minority group.